Age and Gender Related Changes of Femoral Neck-Shaft Angle among Adult Bangladeshi Population by Plain Pelvic Radiograph Study - Bhowmick, Baishakhi; Ashrafuzzaman, Md; Barua, Sharmila; Chowdhury, Urmila; Reza, Rumela; Sumaiya, Sarah Fatima (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Femoral Neck-Shaft Angle (NSA) varies among humans but measurement problems and sampling limitations have precluded the identification of factors contributing to its variation at the population level. NSA varies in relation to age, gender, race, ethnicity lifestyle etc. The aim of the present study was to evaluate the femoral NSA of adult Bangladeshi population by plain pelvic radiograph to build up statistical database and find out any significant difference of femoral NSA among different age group and gender. Materials and methods: This cross sectional observational study was conducted by Department of Anatomy, in the Chittagong Medical College which included 200 Bangladeshi adult came to Radiology Department of Chittagong Medical College and Hospital (CMCH) from different districts. After taking demographic data, plain pelvic X-ray were taken and report was done by an expert radiologist of CMCH. Only normal radiographs were included. Data were analyzed by SPSS version–25. For statistical analysis unpaired student’s ‘t’ test was done and p<0.05 was significant in 95% confidence interval. Results: There is highly significant difference in mean femoral neck-shaft angle of both side in relation to age and gender among different age group of adult Bangladeshi population. Conclusion: Considering the variation of femoral neckshaft angle can help inmanagement of various pathological conditions and fractures of proximal femur, pre-operative selection of prosthetic implants that may improve the overall prognosis of the patients. JCMCTA 2022 ; 33 (2) : 24-29